Biological Response of Positron Emission Tomography Scan Exposure and Adaptive Response in Humans - Kara Schnarr; Timothy F. Carter; Daniel Gillis; Colin Webber; Jennifer A. Lemon; Ian Dayes; Joanna A. Dolling; Karen Gulenchyn; Douglas R. Boreham (SAGE Publishing, 2015)
The biological effects of exposure to radioactive fluorodeoxyglucose ( 18 F-FDG) were investigated in the lymphocytes of patients undergoing positron emission tomography (PET) procedures. Low-dose, radiation-induced cellular responses were measured using 3 different end points: (1) apoptosis; (2) chromosome aberrations; and (3) γH2AX foci formation. The results showed no significant change in lymphocyte apoptosis, or chromosome aberrations, as a result of in vivo 18 F-FDG exposure, and there was no evidence the PET scan modified the apoptotic response of lymphocytes to a subsequent 2 Gy in vitro challenge irradiation. However, lymphocytes sampled from patients following a PET scan showed an average of 22.86% fewer chromosome breaks and 39.16% fewer dicentrics after a subsequent 2 Gy in vitro challenge irradiation. The effect of 18 F-FDG exposure on phosphorylation of histone H2AX (γH2AX) in lymphocytes of patients showed a varied response between individuals. The relationship between γH2AX foci formation and increasing activity of 18 F-FDG was not directly proportional to dose. This variation is most likely attributed to differences in the factors that combine to constitute an individual's radiation response. In summary, the results of this study indicate 18 F-FDG PET scans may not be detrimental but can elicit variable responses between individuals and can modify cellular response to subsequent radiation exposures.